2021
DOI: 10.1108/jet-11-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Technology options to help people with dementia or acquired cognitive impairment perform multistep daily tasks: a scoping review

Abstract: Purpose The purpose of this paper is to review studies that evaluated technology-based prompting systems for supporting participants with dementia or acquired cognitive impairment in their performance of multistep daily tasks. Design/methodology/approach A scoping review was conducted to identify eligible studies through a search of four electronic databases, that is, PubMed, PsycINFO, Web of Science and Institute of Electrical and Electronics Engineers. Findings The search, which covered the 2010–2020 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It should be noted that the idea of using a remotely controlled robot to support a person performing a sequential task is not new (for a review see Lancioni et al, 2021). For instance, Begum et al (2015) conducted an exploratory study in which the robot Ed was used by a teleoperator to provide step-bystep guidance (in the form of audio or audio-visual prompts) to older adults with dementia as they made a cup of tea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the idea of using a remotely controlled robot to support a person performing a sequential task is not new (for a review see Lancioni et al, 2021). For instance, Begum et al (2015) conducted an exploratory study in which the robot Ed was used by a teleoperator to provide step-bystep guidance (in the form of audio or audio-visual prompts) to older adults with dementia as they made a cup of tea.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the idea of using a remotely controlled robot to support a person performing a sequential task is not new (for a review see Lancioni et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research in Human-computer Interaction (HCI) and rehabilitation has focused on providing training tools to people with TBI to enhance their cognitive, sensorimotor, and related living skills. One category of assistive tools provides cognitive support for the memory and attention deficits that tend to follow TBI, which include in-vehicle assistive tools that promote safe driving [80], mobile applications that support meal preparation [84], and tools that provide support in carrying out multi-step tasks [56]. These assistive tools were designed to help individuals with TBI plan and carry out multi-step tasks by prompting them to take the necessary actions.…”
Section: Assistive Technology and Accessibility Options For Individua...mentioning
confidence: 99%
“…These challenges were not a function of lack of experience: most of our participants had used social media platforms for many years before their injuries, so they were already familiar with their functions. However, most TBI training programs focus on teaching basic social media features themselves [23,56]. Instead, when trying to readjust to social media sites, participants requested assistance to compensate for impairments in executive functions such as effective switching of attention, and planning and monitoring of social media activities.…”
Section: Support For Adjusting To Social Media Platforms After Brain ...mentioning
confidence: 99%
“…directions, cues and supplemental information to PwD (Zanwar et al, 2018). Context-aware and augmented reality technology have also been applied to support people with cognitive impairments, including PwD, with performance of tasks that require multiple steps (Lancioni et al, 2021). Klimova et al (2016) examined assistive technologies that are broadly applied to the language disorders of PwD and concluded that especially AAC technologies can significantly improve and substitute the spoken and written communication of PwD.…”
Section: Introductionmentioning
confidence: 99%